2006
DOI: 10.1248/jhs.52.558
|View full text |Cite
|
Sign up to set email alerts
|

Possible Adverse Effects of Soy Isoflavone Mixture on Pregnant and Lactating Rats and their Suckling Pups

Abstract: There is general agreement that soy isoflavones can be beneficial to health in adults. However, isoflavones are well known as endocrine-disrupting chemicals. The possibility that soy foods might adversely affect the reproductive system of mothers and infants should be considered. The aim of this study was to evaluate the adverse effects of a soy isoflavone mixture on rat dams and their offspring. The rat dams were fed diets containing the isoflavone mixture (commercial name: Soyact, aglycone type) at 0, 0.25, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In another study it was emphasized that consumption of soy provided benefits to control lipid levels (Lin et al, 2005). However, it was indicated that raw unprocessed soybean oil contains a toxic factor and it downgrades the growth of rats pups (Ikegami et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In another study it was emphasized that consumption of soy provided benefits to control lipid levels (Lin et al, 2005). However, it was indicated that raw unprocessed soybean oil contains a toxic factor and it downgrades the growth of rats pups (Ikegami et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Until recent, no studies had shown any side effect by taking daidzein supplementation. High doses administration of phytochemical shown no effective effect or may not safeand Ikegami's study showed high-dose isoflavone (1 g per kg body weight) in pregnant mouse related to low birth weight to the fetus [30,31]. Usage of plant-based derived preparations, such as soy isoflavone needs further investigations to reveal its real pharmacological and physiological effect for number of dosage in certain period of administration [32].…”
Section: Discussionmentioning
confidence: 99%
“…Given the rich distribution of oestrogen receptors in female reproductive tissue (Cooke et al 1997, Couse et al 1997, Fitzpatrick et al 1999, Jefferson et al 2002, exposure to phyto-oestrogens can influence oestrogen-related action at the pre-pubertal uterus (Wang et al 2005, Takashima-Sasaki et al 2006 and ovaries (Jefferson et al 2002, Takashima-Sasaki et al 2006). These compounds are also able to cross the placental barrier (Brown & Setchell 2001, Ikegami et al 2006, potentially having a significant effect on prenatal hormonal exposure.…”
Section: Introductionmentioning
confidence: 99%